ATTITUDES OF ELECTRICAL ENGINEERING STUDENTS’ TOWARDS ELECTRONIC SUBJECT AND ITS RELATION TO ACADEMIC ACHIEVEMENT - Salar Karim Fatah; Kurdistan H. Mohammad (Researchers World - International Refereed Social Sciences Journal, 2021)
Attitudes of students toward the lessons is one of the important factors for learning and success. The declining interest in learning among students in a higher institution is a challenge to all. this study aims to investigate the attitudes toward Electronic modules and its relation with academic achievement. This study was a descriptive study. The sample was selected by census methods and include all 84 students of the first stage in Kalar Technical Institute/ Sulaimaniyah Polytechnic University- Kurdistan Region of Iraq in the academic year (2014-2015). A questionnaire was made by researchers for data collection. It consisted of (21) items and the achievement test related to the theoretical and practical aspect of the electronic subject. The questionnaire was applied after having verifying its validity and reliability on a small sample of 25 students Data were analysis by spss22. Findings showed that there is a positive attitude toward the electronic subjects. Also, there is a significant correlation between the students’ attitudes towards the electronic subjects and the collection (practical part) but no statistically significant with the achievement (the theoretical part) of the same subject. There was statistical significance between gender attitude toward Electronic subject. (α= 0.05). there is a relationship between students’ attitudes toward the electronic subject practical part but, there is no relationship between the attitudes and achievement for theoretical part.